THE REAL AND THE FABRICATED IN THE SCREENPLAY “THE STATION OF FOSSIL MAN” - Azatyan, Shmavon (PEOPLE: International Journal of Social Sciences, 2017)
My PhD project consists of a screenplay and exegesis. The exegesis examines the issues of marriage and sexuality that are explored in the screenplay as subjects of disagreement between the old and new generations of intelligentsia in post-Soviet Armenia. This paper presents those sections from the exegesis, which investigate how this historical moment is reflected in my screenplay in terms of verisimilitude. I claim the representation of the Armenian intelligentsia in my screenplay is in the spirit of “authentic realism”. Reflecting on the real and the imagined in the narrative of my screenplay, I argue that there is “critical information,” directly based on the actual, that helps a writer create realistic fiction. I put forth a theory that the narrative discourse in my screenplay consists of two levels – fundamental and fictive, the former representing the real in the narrative, while the latter – the imagined. Using this theory I suggest that the degradation of the Armenian intelligentsia embodied by the protagonist in the screenplay captures realistically the actual cultural moment in post-Soviet Armenia.